Shalat sebagai Psikoterapi Islami dalam Mengatasi Gangguan Kecemasan di Tengah Tren Terapi Alternatif - Saputra, Renaldi (Institut Agama Islam Negeri Parepare, 2024)
This article examines the effectiveness of shalat (Islamic prayer) as a therapeutic intervention in reducing anxiety among individuals with psychological disorders. The study uses a mixed-methods approach, combining quantitative surveys and qualitative interviews, with a research design that integrates numerical and narrative data analysis to provide a comprehensive overview of the impact of shalat. The findings indicate that shalat significantly reduces anxiety levels, with an average decrease of 25% among participants who regularly engage in the practice. Additionally, shalat enhances overall mental well-being, accelerates psychological recovery, and strengthens spiritual resilience. Factors such as the frequency of prayer, the quality of khusyuk (focused devotion), and a supportive environment are crucial to the therapy's effectiveness. The data show that participants who perform shalat with deep focus in a calm environment report more positive outcomes. These findings support the potential of shalat as a supplementary method in anxiety therapy, offering an integrative and spiritual alternative for mental health treatment.